3(2s-3)=-(7-s)
6s-9 = -7+s
5s=2
s=2/5
2006-11-27 10:10:53
·
answer #1
·
answered by maegical 4
·
0⤊
0⤋
s=3
2006-11-27 18:12:27
·
answer #2
·
answered by mnayr22 2
·
0⤊
0⤋
3( 2s - 3) = - (7 - s)
6s-9 = -7+s
5s-9 = -7
5s = 2
s=2/5
2006-11-27 18:22:20
·
answer #3
·
answered by Anonymous
·
0⤊
0⤋
6s - 9 = -7 + s
5s = 2
s = 2/5
2006-11-27 18:11:14
·
answer #4
·
answered by DanE 7
·
0⤊
0⤋
3(2s-3) = -(7-s)
6s-9 = -7+s
5s = 2
s= 2/5
2006-11-27 18:11:30
·
answer #5
·
answered by Green Tea 3
·
0⤊
0⤋
6s - 9 = s - 7
5s = 2
s = 2/5 or 0.40
2006-11-27 18:18:57
·
answer #6
·
answered by Steve P 5
·
0⤊
0⤋
6s-9=-7+s
+9 +9
6s=16+s
-s -s
5s=16
--- -----
5 5
s= 3.2
their you go
2006-11-27 18:13:47
·
answer #7
·
answered by Anonymous
·
0⤊
0⤋
.4
2006-11-27 18:11:50
·
answer #8
·
answered by aznwangstaaa 2
·
0⤊
0⤋
the first guy is right........give me the best awnser...i checked it for you!!!
2006-11-27 18:12:09
·
answer #9
·
answered by da ndn dude 2
·
0⤊
0⤋
how old are you?
2006-11-27 18:11:45
·
answer #10
·
answered by ar_g_2005 2
·
0⤊
0⤋